1991
DOI: 10.1007/bf02536596
|View full text |Cite
|
Sign up to set email alerts
|

Acylation of lyso platelet‐activating factor by splenocytes of the rainbow trout,Oncorhyncus mykiss

Abstract: In mammalian systems, platelet-activating factor, 1-O-alkyl-2-acetyl-sn-glycero-3-phosphocholine, (PAF) is rapidly inactivated by a deacetylation/reacylation system that produces 1-O-alkyl-2-acyl-sn-glycero-3-phosphocholine which is highly enriched in arachidonic acid. There is some evidence that n-3 fatty acids may have an impact on this system in humans but the nature of this impact is unclear. In rainbow trout, n-3 fatty acids are known to be essential dietary components which are derived through the food c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1993
1993
1999
1999

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 37 publications
0
1
0
Order By: Relevance
“…The fatty acid specificity in the acylation of lysoPAF was not significantly different in either domain of the endoplasmic reticulum. Pool et al (1991) have also shown the acylation specificity of lysoPAF in intact and membrane preparations of splenocytes from rainbow trout to be highly specific for omega-3 fatty acids. Samples (1992) concluded that the acetyltransferase in rainbow trout leukocytes will utilize exogenously added, unlabeled lysoPAF to synthesize radio-labeled l-alkyl-2-[ 3 H]acetyl-GPC.…”
Section: Localizationmentioning
confidence: 99%
“…The fatty acid specificity in the acylation of lysoPAF was not significantly different in either domain of the endoplasmic reticulum. Pool et al (1991) have also shown the acylation specificity of lysoPAF in intact and membrane preparations of splenocytes from rainbow trout to be highly specific for omega-3 fatty acids. Samples (1992) concluded that the acetyltransferase in rainbow trout leukocytes will utilize exogenously added, unlabeled lysoPAF to synthesize radio-labeled l-alkyl-2-[ 3 H]acetyl-GPC.…”
Section: Localizationmentioning
confidence: 99%